Developing Supporting Reading Materials for English Subject - Nur Hidayat; Slamet Setiawan (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2020)
The objective of this study is to develop a supporting reading material for junior high school of grade seven based on Curriculum 2013 in Indonesia. The product of this research was a supporting reading material in the form of software and CD to support the main course-book. The instructional design was used the research and development (R&D) model proposed by Branch which was popular as ADDIE (analyze, design, develop, implement and evaluate). It consisted of five steps; (1) analyzing, (2) designing, (3) developing (4) implementing, (5) and evaluating. The participants of product try-out were 30 students and 3 teachers of an Islamic junior high school in Gresik. To validate the product, the reviews of experts, students, and English teachers were provided. The result showed that supporting reading material was accepted and appropriate for the students grade seven in junior high level. It also motivates the students to learn English more and improve their reading skill.